TYPES OF CHORAL INTERPRETATION: AN INTERRELATION OF LITERARY AND MUSICAL COMPONENTS - Білогубка, А. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article raises the problem of choral interpretation of music works of different genres; pays attention to the interrelation of their poetic and sound polyphony, makes an attempt to define leading types of artistic treatment. On the rich material of choral singing, presented by works of Ukrainian and foreign authors, two kinds of choral art as dominant ones are singled out, two types of performing mastery are projected then.